The possibility of base erosion and profit shifting through special economic zones: A critique of the South African and Kenyan SEZ regimes based on BEPS action 5 - Chimbombi, Ame Rebecca (Department of Finance and Tax, 2017)
The OECD/G20's Base Erosion and Profit Shifting (BEPS) Project has been described as the most significant international tax initiative post the 2008/2009 global economic crisis. BEPS speaks to companies engaging in aggressive tax planning strategies that exploit loopholes in tax systems to make profits 'disappear' or shift them to tax jurisdictions with little or no overall corporate tax. The BEPS Project has fifteen Actions targeting various formations, computations and permutations that could potentially give rise to BEPS. BEPS Action 5 is entitled "Countering Harmful Tax Practices More Effectively Taking into Account Transparency and Substance" and is of central importance to this minor dissertation. Special Economic Zones (SEZs) are a creature of international trade law that refers to spatially delimited areas within an economy afforded favourable administrative, regulatory and fiscal benefits when compared to the rest of the economy. The term SEZ is used as an 'umbrella' or 'label' encompassing various types of spatially delimited areas with favourable conditions. Examples of SEZs are Free Trade Zones (FTZs) and Export Processing Zones (EPZs). Although this minor-dissertation focuses mainly on tax benefits associated with SEZs, SEZs usually encompasses a wider range of benefits to the companies they host. Such other benefits could include a one-stop shop for setting up and processing work permits. This minor-dissertation examines whether South Africa and Kenya's SEZs create conducive environments for harmful tax practices in light of and as described in BEPS Action 5.